Advances in Small Perovskite‐Based Lasers. Issue 9 (9th August 2017) - Zhang, Qing; Su, Rui; Du, Wenna; Liu, Xinfeng; Zhao, Liyun; Ha, Son Tung; Xiong, Qihua
Abstract : Lead halide perovskites have recently become a rapidly growing research field due to their great potential in next‐generation solar cells and photonic sources. As a direct bandgap semiconductor, perovskites are also promising candidates for low‐threshold and multicolor lasing devices due to their high optical gain, ease of bandgap engineering, large absorption coefficient, and low defect state density. In particular, reduced‐dimensional perovskite structures including nanoplatelets, nanowires, and quantum dots, are crucial for the development of micro‐ or nanosized laser sources for optical chips and high‐resolution imaging, etc. Here, perovskite nanophotonics, in particular the lasing properties of perovskite nanostructures, are discussed. The rapid advances of small lasers based on perovskite nanostructures using both active and passive microcavities are reviewed; these are mainly classified into four sections: thin films, nanoplatelets, nanowires, and quantum dots. Lasing performance in terms of threshold, color‐tunability, spectral coherence, and stability is introduced from both materials and microcavity respects. Fundamental photophysical mechanisms involved in the photoluminescence lasing process, from absorption, emission to gain, are discussed in order to provide insightful understanding lasing properties of different types of perovskites. Finally, some future prospects for perovskite lasing devices are provided. Abstract : Recent advances in small lasers based on metal halide perovskites, including thin films, nanoplatelets, nanowires, and quantum dots, are highlighted. The fundamental photophysics, materials fabrication, optical‐cavity design, and device characterization are discussed, toward small high‐performance lasers, with low threshold, wide tunability, high spectral coherence, and good stability.